AKR2A interacts with KCS1 to improve VLCFAs contents and chilling tolerance of Arabidopsis thaliana. (23rd June 2020) - Chen, Lin; Hu, Wenjun; Mishra, Neelam; Wei, Jia; Lu, Hongling; Hou, Yuqi; Qiu, Xiaoyun; Yu, Shaofang; Wang, Changlu; Zhang, Hong; Cai, Yifan; Sun, Chunyan; et al.
Summary: Arabidopsis thaliana AKR2A plays an important role in plant responses to cold stress. However, its exact function in plant resistance to cold stress remains unclear. In the present study, we found that the contents of very long‐chain fatty acids (VLCFAs) in akr2a mutants were decreased, and the expression level of KCS1 was also reduced. Overexpression of KCS1 in the akr2a mutants could enhance VLCFAs contents and chilling tolerance. Yeast‐2‐hybrid and bimolecular fluorescence complementation (BIFC) results showed that the transmembrane motif of KCS1 interacts with the PEST motif of AKR2A both in vitro and in vivo . Overexpression of KCS1 in akr2a mutants rescued akr2a mutant phenotypes, including chilling sensitivity and a decrease of VLCFAs contents. Moreover, the transgenic plants co‐overexpressing AKR2A and KCS1 exhibited a greater chilling tolerance than the plants overexpressing AKR2A or KCS1 alone, as well as the wild‐type. AKR2A knockdown and kcs1 knockout mutants showed the worst performance under chilling conditions. These results indicate that AKR2A is involved in chilling tolerance via an interaction with KCS1 to affect VLCFA biosynthesis in Arabidopsis . Significance Statement: AKR2A is positively involved in chilling tolerance by interacting with KCS1 to regulate VLCFA biosynthesis in Arabidopsis.